2013
DOI: 10.1128/mcb.00723-13
|View full text |Cite
|
Sign up to set email alerts
|

Protein Inhibitor of Activated STAT 1 (PIAS1) Is Identified as the SUMO E3 Ligase of CCAAT/Enhancer-Binding Protein β (C/EBPβ) during Adipogenesis

Abstract: bIt is well recognized that PIAS1, a SUMO (small ubiquitin-like modifier) E3 ligase, modulates such cellular processes as cell proliferation, DNA damage responses, and inflammation responses. Recent studies have shown that PIAS1 also plays a part in cell differentiation. However, the role of PIAS1 in adipocyte differentiation remains unknown. CCAAT/enhancer-binding protein ␤ (C/EBP␤), a major regulator of adipogenesis, is a target of SUMOylation, but the E3 ligase responsible for the SUMOylation of C/EBP␤ has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 50 publications
(66 reference statements)
0
50
0
Order By: Relevance
“…However, little is known about food factors which promote the degradation of C/EBP␤ protein. C/ EBP␤ protein is degraded by the proteasome pathway through increasing its ubiquitination (41). Our results showed that CCM promoted ubiquitination of C/EBP␤ (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…However, little is known about food factors which promote the degradation of C/EBP␤ protein. C/ EBP␤ protein is degraded by the proteasome pathway through increasing its ubiquitination (41). Our results showed that CCM promoted ubiquitination of C/EBP␤ (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…At 2 days postconfluence (designated day 0), 3T3-L1 were subjected to adipogenic differentiation as previously described (22). Adipocytes phenotype appeared on day 3 and reached maximum by day 8 postadipogenic induction.…”
Section: Reagent and Adipocyte Differentiationmentioning
confidence: 99%
“…Our previous report clarified that PIAS1 restricted adipocytes differentiation by inhibiting CCAAT-enhancerbinding protein-b (22); however, the function of PIAS1 in mature adipocytes is not clear yet. In the current study, we found that PIAS1 was downregulated in the inguinal white adipose tissue (iWAT) of prediabetic models, including leptin-deficient (ob/ob), leptin receptor-deficient (db/db), and high-fat diet (HFD) mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dutchak et al (22) reported that FGF21 knockout mice have a marked increase in the SUMOylation of PPAR␥ and decreased body fat, indicating that SUMOylation of PPAR␥ modulates adipogenesis. Liu et al (23) found that PIAS1 promotes C/EBP␤ SUMOylation and inhibits adipogenesis. Chung et al (24) found that a de-SUMOylation protease, SENP2, can directly modulate C/EBP␤ SUMOylation and its stability and, consequently, is essential for adipogenesis.…”
Section: Discussionmentioning
confidence: 99%